Pemanfaatan Arang Sebagai Media Penahan Air Untuk Mendukung Pertumbuhan Bibit Sukun Di Daerah Tangkapan Air Danau Toba, Kabupaten Simalungun - Adelina Sitompul; Budi Utomo; Afifuddin Dalimunthe (Peronema Forestry Science Journal, 2015)
Forests and land in the catchment area of TobaLake  showed a decrease for  quality and quantity of the land. This study aims to identify the breadfruit seeds (Artocarpus communis Forst) for the growth responseagainst granting additional material to the growing media in the form of water retaining material. This research was conductedinthe Catchment Area of Toba Lake, Simalungun district.The result showed that the interaction of charcoal dose treatment did not significantly affect the mean height increament, diameter, number of leaves, water content, leaf area, and spacious canopy.Keywords: Breadfruit (Artocarpus communis Forst), charcoal